ADJECTIVE AND VERB CONJUGATION IN ANCIENT TURKISH RUNIC MONUMENTS - Yadigar Veli oglu Aliyev (Research Retrieval and Academic Letters, 2024)
As a rule, among the non-degradable forms of the verb, adjectives and verbs are predominant. A verbal adjective has the basic characteristics of a verb and an adjective. The verb binding has the main signs of the verb and the adverb. Most of the suffixes related to the verb adjective and verb binding were used in the ancient Turkish language. Few of them are observed in modern Turkic languages, including modern Azerbaijani language. The study of them is of great importance from the point of view of the history of Turkic languages.